DEVELOPMENT STRATEGY TO IMPROVE THE QUALITY RESULTS OF EDUCATION IN THE ADMINISTRATIVE SUPPORT OF THE NAVAL EDUCATION CENTRE - Khristian Gunawan Aden; Udisubakti Cipto Mulyono; Adi Bandono (JOURNAL ASRO, 2022)
The Indonesian National Armed Forces as the front line of national defense must implement policies that are inline with those conveyed by emphasizing the ranks in order to carry out appropriate budgetary activities, especiallythose that are right on target for predetermined uses. The use of the budget must optimize the control side ofactivities, the fulfillment of the procurement of goods and services as well as the maintenance of defenseequipment, the fulfillment of targeted supplies, as well as personnel management, and updating of educationalinstitutions. The Navy Education Centre For Administrative Support is an instructive institution for the Naval forcewhich is the center for authoritative help instruction and has an imperative part in regulatory help instruction. Thereason for this consideration was to decide on elective techniques for creating authoritative help instruction centersin arrange to move forward the quality of prepared warriors utilizing the SWOT strategy. The comes about ofdistinguishing proof are 10 (ten) internal variables with 4 (four) strength variables and 6 (seven) weaknessvariables, and 10 (ten) external components with 3 (eight) opportunity components and 7 (seven) Threatcomponents. The chosen strategy may be a strength-threat procedure that suggests maximizing the change ofdebilitating variables by utilizing qualities within the frame of concentric expansion, with 4 (five) ST methodologiesproduced, and then weighting all of obtain strategy with the Borda method and making the roadmap from prioritystrategy. Keywords: SWOT, Borda, roadmap, education, administrative support